Effect of hip adduction/abduction contraction on pelvic floor in young healthy women - Hiroyo Kamio; Hitoshi Maruyama; Nozomi Ito; Mako Kunieda; Ayaka Chiba; Yorimitsu Furukawa (Japanese Society of Physical Fitness and Sports Medicine, 2022)
Pelvic floor muscle training has been reported to be effective in preventing and improving urinary incontinence. Patients must learn to perform pelvic floor muscle contractions without pushing down the pelvic floor by contracting other muscle groups. This study aimed to determine the effect of maximal-effort contraction of the hip adductor and abductor muscles on the pelvic floor of young, healthy women. For these experiments, 23 healthy nulliparous women performed unilateral maximal-effort isometric contractions of the abductor and adductor hip muscles in a supine position. Simultaneously, the movement of the bladder's posterior surface was measured using an ultrasonic imaging device. The displacement of the bladder base during maximal-effort contraction of the hip adductor/abductor muscles was calculated based on changes in the distance between the abdominal wall and the bladder base at rest. The results demonstrated that the bladder base significantly descended during maximal-effort isometric contraction of hip adduction/abduction. The maximal-effort isometric hip adduction/abduction muscle strength positively correlated with bladder base descent. These results indicated that isometric contraction of the hip adduction/abduction muscles under maximum effort pushed the pelvic floor downward. In pelvic floor muscle training, when the adductor and abductor muscles of the hip joint are contracted with maximum effort, the pelvic floor muscles cannot learn contraction and may inhibit movement.